The position of Tantrayuktis tools for writing and recognizing treaties in Indian research methodology: Array - Sharma , Puneet (Ayurline: International Journal of Research in Indian Medicine, 2020)
Meemansa (name of the pattern of philosophy), Nyaya (name of the phase of philosophy) and Vyakarana (grammar) are used for the proper interpretation of Vedas. Vaidya was expected to have knowledge of Sankhya, Jyotish Shastra and Vaisheshika, etc. Being part of Vaidic literature, Meemansa, Nyaya and Vyakarana are also most important for the proper interpretation of Ayurveda. Controversial scientific theories have been practiced in public in India since ancient times. Both practices of Indian SÄstrakaras are included in the Tantrayukti scheme. Tantrayukti is used in many ancient philosophical forms of literature, such as Governance, Ayurveda, AlankÄra, NyÄya, MÄ«mÄnsa, KÄmaÅ›Ästra and VyÄkarana. These all provide us an impression of the scientific methodology to be followed and implemented in the respective works. Yet Ayurveda has established its own special technique for proper interpretation, named Tantrayukti, in which certain important points of this Darshana or other sciences have already been integrated. Tantraukti is the philosophy or strategy or systematic approach to the analysis of Tantra (science) in order to translate its right, unmistakable meaning for a specific practical application.